A Randomized Controlled Trial of a Multimedia Patient Education Tool for Stress Versus Urgency Urinary Incontinence. Issue 9 (September 2021) - Schroeder, Michelle; Plotner, Elisabeth A.; Sharma, Shefali; Hunter, Krystal; Spector, Sean; Lipetskaia, Lioudmila
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:403–408) Using different modalities for patient education can improve patients' understanding of their disease and treatment plans. Multimedia-based patient counseling—which includes images, voice, and animation—may be one alternative to traditional, conversation-based patient counseling of complex medical information.